ENT 530 Social Media Portfolio: Que's Kitchen / Finarioson Timun - Timun, Finarioson (2021)
Que’s Kitchen is to make cookies, cakes, desserts that have their own special features. all cookies, cakes, desserts are made homemade. The advantage of this que's kitchen is that it makes cookies that have a different flavour than the others. Most customers of Que's Kitchen are satisfied with the cookies that have been produced. The owner of this business is madam Quewellyshadore Lewan Inoi. she manages her business on her own. she will use social media platforms to promote and sell her products. at present she only does business online around Bintulu, Sarawak.